2022
DOI: 10.1002/bio.4358
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches of erythrosine B as a food dye‐derived spectroscopic probe for assessing trospium chloride in raw material and dosage form

Abstract: Two facile spectroscopic methodologies were designed for estimating trospium chloride (TPM) in raw material and tablets with high operational reliability and selectivity. The methods were based on using erythrosine B (EB) as a spectroscopic tool for ion-pair complex formation with the drug. In a mild acidic medium of Britton Robinson buffer (pH 4.0), the ionized hydroxyl group in the reagent interacted with the ionized amine in the studied drug. Method I was based on the spectrophotometric measuring of the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It was found that the maximum absorbance was produced at pH 4 (Figure 4). Most studies of EB quenching by basic drugs proceed in the acidic medium [15][16][17][18]. Different volumes of BR buffer (0.3-2.0 mL) at pH 4 were examined.…”
Section: Buffer Ph and Volumementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the maximum absorbance was produced at pH 4 (Figure 4). Most studies of EB quenching by basic drugs proceed in the acidic medium [15][16][17][18]. Different volumes of BR buffer (0.3-2.0 mL) at pH 4 were examined.…”
Section: Buffer Ph and Volumementioning
confidence: 99%
“…Based on its chemical structure, it is an acidic dye that can form ion-pair complexes with basic amino compounds such as BIP. For instance, it has been employed for spectrofluorimetric and spectrophotometric determination of albendazole [14], benzimidazole [15], varenicline [16], trospium chloride [17], tamoxifen [18], sunitinib [19], rupatadine [20], and naftidrofuryl [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, xanthene dyes (eosin Y, erythrosin B, fluorescein, merbromin) have been used as colorimetric, fluorescent, and/or RRS analytical reagents for determining a wide range of active pharmaceutical ingredients [12]. For example, eosin Y and merbromin dyes have been reported for determining daclatasvir, cyclobenzaprine, fluvoxamine, atomoxetine, oxybutynin, dexlansoprazole and some β-blockers [13][14][15][16][17][18][19], while erythrosin B has been utilized for determining rupatadine, duloxetine, terbinafine, venlafaxine, nilotinib trospium, and varenicline [20][21][22][23][24][25][26]. The benefits of using erythrosin B include its low price and a high degree of stability.…”
Section: Introductionmentioning
confidence: 99%